The association of organisational culture and organisational commitment with job satisfaction: perspective of the Malaysian vegetable oil processing sector / Prayashini Prabhaharan and Azzman Mohamed - Prabhaharan, Prayashini; Mohamed, Azzman (Universiti Teknologi MARA, 2021)
The present study has sought to contribute to the growing knowledge base pertaining to the increasing trend in the high employee turnover rate in Malaysia's manufacturing industry and challenges faced by organisations in retaining talented workforce arising from the job satisfaction issue. In such a perspective, this study examines the association of organisational culture and organisational commitment with job satisfaction. Insufficient research is available on these associations within the context of the Malaysian vegetable oil processing sector; thus, this study has aimed to add new knowledge to the existing literature. A quantitative research approach, namely a cross-sectional survey, was utilised to gather data from the sample population who were employed in vegetable oil processing factories in Pasir Gudang, Johor. The participants were chosen via the simple random sampling approach. Pearson correlation and linear regression analysis methods were utilised to analyse the associations among the variables. The highest correlation revealed between adhocracy culture and normative commitment. Regression analysis findings demonstrated a positive significant association between all dimension's variables of organisational culture and organisational commitment on job satisfaction. Overall, the study has provided comprehensive insights for the vegetable oil processing organisations to review the culture in their company that could enhance organisational members' commitment and job satisfaction.